Pengaruh Hedonic Shopping Motives, Sales Promotion, Fashion Involvement terhadap Impulse Buying Shopee - Ngadiman, Sabrina; Pradana, Bayu Laksma (Penerbit Goodwood, 2024)
Purpose: Consumer impulse buying has received considerable attention in consumer research. This phenomenon is interesting because it is not only driven by various internal psychological factors but also influenced by external stimuli related to the market. This study aims to determine whether there is an influence between Hedonic Shopping Motives, Sales Promotion, and Fashion Involvement on Impulse Buying of a Pradita University student class of 2020 – 2023 Business Management Study Program, Retail Management, and Accounting, who use Shopee e-commerce. Method: A quantitative survey method was used. The sampling technique used the nonprobability sampling method and purposive sampling, with a total sample of 140 people. Data collection techniques using online questionnaires. Primary and secondary data were used in this study. The analytical tool used in this study was multiple regression using SPSS 26. Results: The results of this research show that Sales Promotion and Fashion Involvement have no effect on impulse buying on the Shopee application, while Hedonic Shopping Motives have a significant positive effect on Impulse Buying among the Pradita University student class 2020 – 2023 Business Management, Retail Management, and Accounting Study Programs that use Shopee e-commerce. Limitation: The limited scope of research focuses only on Pradita University students from 2020 to 2023. Contribution: Fashion involvement has no influence on impulse buying among Pradita University students’ class 2020 – 2023 Business Management, Retail Management, and Accounting Study Programs that use the Shopee application.